Giving what is due to the child born out of rape: Revisiting article 345 (2) of the revised penal code to declare it unconstitutional - Bacolod, Hannah Alyssa B. (Animo Repository, 2017)
The Revised Penal Code provides for the penalties to the person guilty of the crime of rape. The civil liabilities of an offender are stated under Article 345, which sentences him to (1) indemnify the woman, (2) to acknowledge the child born out of the crime, if any, unless the law prevents him from doing so, and (3) to support the said child. With the passage of the Family Code, the child born out of rape is now classified as an illegitimate child, whose rights under the law is vested upon acknowledgment of the putative parent. The issue in Article 345 of the Revised Penal Code is the exception provided for in paragraph 2. The said provision is discriminatory to the said illegitimate child because the rule that has been consistently applied based on jurisprudence is that if the offender is married, he cannot be sentenced to acknowledge the child born out of rape but shall only be sentenced to provide support. The prohibition under Article 345 (2) of the Revised Penal Code is unconstitutional because it violates the said child’s constitutional rights to equal protection clause and right to property, which is his or her right to inherit from his or her putative father’s estate. There is unequal treatment between an illegitimate child born out of rape and an illegitimate child in general. Without acknowledgment the rights of an illegitimate child provided for under the law will not be vested upon him or her, leaving the child born out of rape with an illegitimate status without rights as compared to an acknowledged illegitimate child who enjoys his or her rights under the law. The proponent submits that the said provision should be amended to declare the child of the offender as his illegitimate child, whether he is married or not, to guarantee what is due to the child under the Constitution.